CORRUPTION IN THE MATRIX OF DEVELOPMENT IN NIGERIA - Oghi, Felix Ejukonemu (European Scientific Journal, ESJ, 2013)
In recent times the spate of uncontrolled incidences of corrupt practices in the Nigeria nation-state has assumed threatening dimension that if the malaise is left unchecked, it may be the beginning of the end of a nation-state that its founders toiled assiduously to build. This paper examines the concept of corruption, its forms, propellants and its management. Among other things, the paper also discusses how corruption has affected and negated the developmental strides Nigeria’s “young” democracy and emphasize that some measures should be taken to address the problem.